New methodology shows that 258 million children, adolescents and youth are out of school (UNESCO, 2019)
Three years after the adoption of Sustainable Development Goal 4 (SDG 4) and the promise to provide universal primary and secondary education, there has been no progress in reducing the global number of out-of-school children, adolescents and youth. This fact sheet by the UNESCO Institute for Statistics (UIS) highlights the most recent statistics on trends at the global and regional levels, based on a revised calculation method that provides more precise estimates of the out-of-school population.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; approches et analyses; discipline; femmes*; inégalités; périodes historiques; systèmes d'oppressions; éducation

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field-- such as Tim Wise and Abby Ferber-- with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

De l'égalité des deux sexes - Poulain de la Barre, François (Grandes voix du féminisme, 2010)
François Poulain de la Barre (1647-1723) est un penseur de l'égalité entre les sexes. Exemple de transgression idéologique, il passe du catholicisme au protestantisme « rationnel », de la scolastique à la philosophie nouvelle, du phallocentrisme à la philogynie. Il utilise la méthode de Descartes et sa réflexion sur l'homme pour démontrer cette égalité des sexes, aussi bien d'un point de vue physiologique que psychologique. Cette réflexion s'appuie aussi sur une généalogie de l'humanité qui discute les thèses des théoriciens du droit naturel. Relisant parallèlement des textes souvent utilisés contre les femmes (Aristote et surtout la Bible), Poulain de la Barre apparaît comme un protagoniste essentiel du travail de lecture critique des textes sacrés à l'âge classique, au même titre que Simon ou Spinoza. D'où un vaste programme de réforme sociale, qui fait de l'éducation des femmes la seule voie pour leur émancipation et qui interroge la légitimité des sources traditionnelles d'autorité (le savant, le prêtre, le noble). Souvent cités dans les études anglo-saxonnes (aussi bien en histoire, philosophie, littérature que dans les études de genre).
Keywords: 1600-1699; EDI; approches et analyses; cours; discipline; fem1000; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; éducation; épistémologie